Lenses - Naomi Pinno 1997- (2022)
Each movement of Lenses represents a different perspective. Like the formation of perspectives, the interchange of imitation and contrast has shaped this piece. I have been fascinated by the extreme nature and vibrant culture in Iceland, hence this piece is dedicated to the places and people whose influence enriched my life for the past two years.